THE EFFECT OF GREEN LEADERSHIP, ENVIRONMENTAL AWARENESS, AND WORK ETHICS ON SUSTAINABLE WORK BEHAVIOR: EVIDENCE FROM THE EDUCATION OFFICE OF KERINCI REGENCY - Ice Sastriawati; Laynita Sari (Yayasan Education and Social Center, 2026)
This study aims to analyze the effect of green leadership, environmental awareness, and work ethics on sustainable work behavior among employees of the Education Office of Kerinci Regency. This research employs a quantitative approach using a survey method. The population consists of all employees, with a total sample of 47 respondents using a total sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression analysis with the assistance of statistical software. The results show that green leadership, environmental awareness, and work ethics have a positive and significant effect on sustainable work behavior, both partially and simultaneously. Work ethics is identified as the most dominant variable. The coefficient of determination (R²) is 0.569, indicating that 56.9% of sustainable work behavior is explained by the independent variables, while 43.1% is influenced by other factors. These findings highlight the importance of leadership, awareness, and ethical values in promoting sustainable behavior in public organizations.